Mutu Rusip Pada Lama Fermentasi Yang Berbeda - Dyah Koesoemawardani; Wana Nurlita; Otik Nawansih; Sri Hidayati (Politeknik Negeri Lampung., 2025)
Rusip is a fermented fish product that has a distinctive aroma and taste depending on the fermentation time because it produces peptides and amino acids that contribute to the aroma and taste of rusip. This study aims to determine the optimal fermentation durations to produce rusip with good chemical and functional characteristics. This study used a completely randomized design with 4 replications and 5 treatments of fermentation duration (weeks), namely 0, 1, 2, 3, and 4. The observation parameters included pH, lactic acid bacteria (LAB), peptide content, water content, antioxidant activity, and glutamate acid. The data obtained were statistically analyzed using Barlett's test and Tuckey's test, followed by ANOVA test and Duncan New Multiple Range Test (DNMRT) test at 5% level. The test results on these parameters then selected the best treatment to be tested for protein content. The test results showed that the optimal fermentation time was 3 weeks with a pH of 5.55; moisture content of 62.67%; peptide content of 2.38%; glutamic acid 13.41%; antioxidant activity of 54.75%; the number of LAB 9.51 log CFU/g; and protein content of 15.03%.